A novel animal model of spontaneous epilepsy: Cdk5 knockout in pericyte-specific mice - Lin, Lin; Hu, Xiaofei; Hong, Weijun; Pan, Tengwei; Wang, Zhiren; Wang, En; Wu, Gang (Frontiers in Cellular Neuroscience, 2024)
Changes in neurovascular unit components and their interactions play a crucial role in epileptogenesis and the pathological process of epilepsy. Currently, there is a lack of animal models that can accurately reflect the etiological impact of cerebrovascular lesions on epilepsy. In this study, we constructed Cdk5 conditional knockout mice in Cspg4 (pericyte marker)-positive cells using the Cre-LoxP system. The results revealed that this strain of mice exhibited significant seizure behaviors and epileptiform brain waves, loss of hippocampal and amygdala neurons, astrogliosis, decreased pericyte coverage, and reduced AQP4 polar distribution. Herein, we have developed a novel mouse model of spontaneous epilepsy, providing a critical animal model for studying the involvement of neurovascular unit factors in the development and progression of epilepsy.